Determinación del contenido de polifenoles del extracto y fracciones de Bursera tomentosa, y su efecto en la viabilidad celular sobre células SiHa. - Ortiz Perdomo, Sebastian Camilo (Universidad Antonio Nariño, 2023)
Research on natural products is constantly searching for molecules with biological activity that may represent an alternative to modern treatments, leading to the identification of compounds in littlestudied plant species, such as the Bursera tomentosa species. Where it was determined qualitatively, by means of phytochemical screening, which has triterpenes, flavonoids, phenols, tannins and alkaloids in its chemical profile. It was found that the polyphenol content in the crude extract is 129.49 ± 11 mg/g equivalents of gallic acid, through the Folin-Ciocalteau test. In the evaluation of biological activity, the extract and the ethyl acetate, ethanol and aqueous fractions, against the SiHa cell line, managed to reduce the percentage of survival below 50%, in contrast to the effect on the vero cell line, where this effect was only evidenced for the ethyl acetate fraction